THE STRUCTURAL COMPOSITION AND TYPOLOGY OF FEMALE OFFENDERS - Dilshoda O’rinova Adkhamovna (International Journal of Business, Law and Political Science, 2025)
Objective: This study aims to analyze the structural composition and typological classification of female offenders by identifying patterns based on behavior, social background, and crime characteristics. Method: The research employs a qualitative approach, synthesizing theoretical frameworks and empirical studies from established criminological literature to develop a structured typology of female criminality. Results: The analysis reveals that female offenders can be systematically grouped into specific categories that reflect distinct socio-psychological and economic influences. These typologies provide valuable insights into the underlying factors driving women’s involvement in criminal activity, highlighting both individual motivations and broader systemic issues. The study also identifies critical shortcomings in current criminal justice responses to female offenders, particularly in the areas of prevention and rehabilitation. Novelty: Unlike existing studies that often generalize offender profiles, this research emphasizes a gender-sensitive approach by integrating multiple dimensions—behavioral, social, and economic—into a cohesive typological framework. It proposes practical, evidence-based recommendations for improving policies and programs that address the unique needs of female offenders, thereby contributing to the refinement of criminological theory and justice system practices.